From Nobilissima dux to Beata: expressions of female authority and influence in medieval Florence - Smith, Barbara S., author; Lindsay, James E., advisor; Didier, John, committee member; Coronel, Patricia, committee member (Colorado State University. Libraries, 2013)
This thesis argues that by examining four influential women of Florence and northern Italy over some five centuries' time (circa 1060-1471A.D.) historians can view change over time related to female authority and how it reflects larger social norms that became increasingly entrenched over time. These women inform our understanding of the role and status of women in medieval Florence through their exceptionality. By considering such a large expanse of time these women's lives can be compared to one another, as well as to their contemporaries. Chapter 1 introduces the topic and discusses general themes that are occurring contemporaneously across Europe that serve to inform and provide context for the laws and social norms that are occurring in Florence. Chapter 2 focuses more directly on each woman and her familial and social circumstances in which she uses and exercises her authority. Chapter 3 builds on the base of Chapter 2 and makes arguments regarding the extent to which each woman wielded her authority and the ways in which that authority was exercised. Chapter 4 provides a brief conclusion in relation to each woman and how the four, together, help to inform historians' knowledge about the ways in which patriarchal power structures, including patrilineage, worked to increasingly exclude women from positions of authority.
Keywords: women; authority; Florence; Italy; saints